The role of the superior parietal lobule in lexical processing of sign language: Insights from fMRI and TMS. (February 2021) - Banaszkiewicz, A.; Bola, Ł.; Matuszewski, J.; Szczepanik, M.; Kossowski, B.; Mostowski, P.; Rutkowski, P.; Śliwińska, M.; Jednoróg, K.; Emmorey, K.; Marchewka, A.
Abstract: There is strong evidence that neuronal bases for language processing are remarkably similar for sign and spoken languages. However, as meanings and linguistic structures of sign languages are coded in movement and space and decoded through vision, differences are also present, predominantly in occipitotemporal and parietal areas, such as superior parietal lobule (SPL). Whether the involvement of SPL reflects domain-general visuospatial attention or processes specific to sign language comprehension remains an open question. Here we conducted two experiments to investigate the role of SPL and the laterality of its engagement in sign language lexical processing. First, using unique longitudinal and between-group designs we mapped brain responses to sign language in hearing late learners and deaf signers. Second, using transcranial magnetic stimulation (TMS) in both groups we tested the behavioural relevance of SPL's engagement and its lateralisation during sign language comprehension. SPL activation in hearing participants was observed in the right hemisphere before and bilaterally after the sign language course. Additionally, after the course hearing learners exhibited greater activation in the occipital cortex and left SPL than deaf signers. TMS applied to the right SPL decreased accuracy in both hearing learners and deaf signers. Stimulation of the left SPL decreased accuracy only in hearing learners. Our results suggest that right SPL might be involved in visuospatial attention while left SPL might support phonological decoding of signs in non-proficient signers.